Relationship between academic self-concept and self-esteem among student-athletes / Norzila Yusoff ... [et al.] - Fresco, Fresh David; Vincent, Parnabas (Faculty of Sports Science and Recreation, 2014)
Purpose of this study was to determine the relationship between academic self-concept and selfesteem among student-athletes. The level of academic self-concept was collected using the Liu and Wang’s (2005) Academic Self-Concept Scale which consists of Academic Confident (AC) and Academic Effort (AE), whereas The Rosenberg’s (1965) Self-esteem Scale was used to measure self-esteem. This study was conducted on 52 athletes (male = 33 and female =19) during the tournament of Malaysian University Sports Council (MASUM) which was held at Hang Jebat Sports Complex, Melaka. The results had showed that males athletes had slightly higher of Academic Self-Concept (mean = 64.60) compared to females (mean = 63.37). However, females athletes (mean = 20.32) exhibited higher level of self-esteem higher than males athletes (mean = 18.78). Meanwhile the correlation result on academic self-concept and self-esteem showed there was a small negative correlation (r = .17) but there is no significant relationship between both variables among university athletes (p < 0.05). It concluded that academic self-concept and self-esteem played important roles for the student-athletes to success in academic and sports.